The synthesis of control algorithm over a technical condition of the hydrogen generators based on hydroreactive compositions - Abramov, Yuriy; Basmanov, Oleksii; Krivtsova, Valentina; Mikhayluk, Andrey (Eastern-European Journal of Enterprise Technologies, 2018)
We have synthesized a control algorithm over technical condition of the hydrogen generators, which includes the following: forming initial data, determining the values for a phase-frequency characteristic of the generator at control points, comparing the a priori assigned and measured values of the phase-frequency characteristic of a hydrogen generator at control points in accordance with the selected criterion. When describing the dynamic characteristics of a hydrogen generator based on hydro-reactive compositions we used an integrated transfer function, for which an analytical expression was obtained. Taking into consideration the properties of an integrated transfer function of the hydrogen generator, we justified the selection of control points that define initial data for constructing a hydrogen generator control algorithm. Control points are characterized by the fact that at these points the algebraic components of an integrated transfer function of the hydrogen generator coincide by modulo, or each of them tends to zero. As a criterion for determining a technical condition of the hydrogen generator, according to the control algorithm, we employed a system of inequalities, built for control points. The system of inequalities includes the a priori assigned values for a phase-frequency characteristic of the hydrogen generator and its values measured under condition of using a reaction of the generator to a test influence in the form of a jump change in the area of its outlet opening. Solving the test problem revealed that a methodological relative accuracy in determining a phase-frequency characteristic under these conditions does not exceed 3.7 %. Frequency acts as a parameter for control points. It is shown that the values of these frequencies are the solutions to a system of algebraic equations whose parameters are the time constants of a hydrogen generator.